Refining interconnected financial reporting practices and procedures of the central and field Philippine accounting offices to enhance accuracy, reliability, and uniformity of consolidated financial statements - Angeles, Princess Minesa (Animo Repository, 2023)
National Government Agencies (NGAs) in the Philippines are machinery that is responsible for the oversight and administration of specific functions. Support services, including accounting and other administrative services, are essential to enable these agencies to perform their mandates. Considering that NGAs are funded by tax collections from various sources, they are accountable for their proper utilization and public reporting. Through the annual publication of financial statements, citizens can get a picture of its operations and assess how funds are being managed. In addition, the accompanying audit opinion certifies if it is correct and reliable. This action research intended to strengthen the integrity and credibility of the Philippine Statistics Authority (PSA) in terms of excellent financial reporting procedures. We would also like to address recurring issues that bring about unfavorable financial audit results and improve our existing processes. Different action research tools such as first, second, and third-person practices were utilized to ensure fruitful involvement of concerned colleagues. Established financial reporting practices of governments of other countries were also looked into and determined its applicability in the Philippine context. Moreover, Lewin’s Change Model, in conjunction with the Force Field Analysis, allowed decrease in resistance and sustain change. Above all, we instilled the spirit of collaboration across PSA offices to guarantee that we collectively tackle setbacks and keep team spirit. Keywords: Action Research, Financial Statements, Financial Reporting, Audit Opinion, Review of FS, Reliability, Uniformity, Accuracy